2013
DOI: 10.1016/j.nanoen.2012.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Tunable synthesis of (Mg–Ni)-based hydrides nanoconfined in templated carbon studied by in situ synchrotron diffraction

Abstract: The formation of ultra-small Mg-based particles nanoconfined into the mesopores of a carbon template was studied by in situ synchrotron diffraction. Either Mg 2 Ni or Mg 2 NiH 4 nanoparticles can be directly formed starting from separate Ni and MgH 2 species by tuning the H 2 pressure. Both ultra-small Mg 2 Ni and Mg 2 NiH 4 nanoparticles (~4 nm) are extremely stable against coalescence during hydrogen sorption cycling and prolonged exposure to high temperature as compared to Mg and MgH 2 nanoparticles that sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…The work of Zlotea et al [64] showed that contrary to MgH 2 , the size of the nanoparticles of Mg 2 NiH 4 is not affected by sorption cycling nor by high temperature. Indeed, Fig.…”
Section: Nanoconfinementmentioning
confidence: 98%
See 2 more Smart Citations
“…The work of Zlotea et al [64] showed that contrary to MgH 2 , the size of the nanoparticles of Mg 2 NiH 4 is not affected by sorption cycling nor by high temperature. Indeed, Fig.…”
Section: Nanoconfinementmentioning
confidence: 98%
“…To modify the sorption properties of magnesium or magnesium alloys, the use of particle confinement [62][63][64][65] has been proposed. By increasing the surface-to-bulk atomic ratio, changes in the thermodynamics are foreseen.…”
Section: Nanoconfinementmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the earliest reports is on Mg 2 NiH 4 , formed by the deposition of Mg into the pores of a carbon scaffold that already contained Ni nanoparticles [135]. The resulting *4 nm Mg 2 Ni and Mg 2 NiH 4 nanoparticles were very stable upon cycling, with sorption being achieved within 5 min at 210°C [136]. Magnesium boron hydrides were prepared by the pre-deposition of Mg nanoparticles, followed by an exclusively pore-confined reaction (because of the high reactivity of the pore-confined nanoparticles) with diborane [137,138].…”
Section: Strategies To Prepare Nanoconfined Materialsmentioning
confidence: 99%
“…In this context, the main improvements achieved so far through nanoconfinement have been in terms of hydrogen kinetics. The carbon scaffold is also expected to limit the growth of the Mg nanoparticles upon hydrogen cycling and, thus, lead to stable hydrogen kinetics (Zlotea et al, 2013). Currently, Mg nanoconfinement with carbon materials is usually done via melt infiltration or thermal decomposition of an Mg precursor initially impregnated in the porosity of the carbon scaffold (Konarova et al, 2012;Liu et al, 2014).…”
mentioning
confidence: 99%